The Link between HLA-B Alleles and Causative Drugs in Vietnamese Patients with Stevens-Johnson Syndrome/Toxic Epidermal Necrolysis - Huyen, Tran Thi; Hoa, Pham Dinh; Trang, Trinh Minh; Khanh, Nguyen Ba; Que, Tran Ngoc; Phuong, Nguyen Hoang; Hoang, Nguyen Minh; Abe, Riichiro; Thuong, Nguyen Van; Lan, Pham Thi; Tirant, Michael (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are severe cutaneous adverse drug reactions. Human leukocyte antigens (HLA) may play an important role in the pathogenesis of SJS/TEN. AIMS: This study aims to identify HLA-B alleles in Vietnamese patients with SJS/TEN and to investigate the possible link between HLA-B alleles and causative drugs. MATERIALS AND METHODS: Sixty patients including SJS (30 patients) and TEN (30 patients) were enrolled in a cross-sectional descriptive study at two hospitals in Hanoi, Vietnam, from July 2018 to July 2019. Clinical features and laboratory findings were noted, HLA-B alleles were analyzed by the polymerase chain reaction (PCR)-sequence-specific oligonucleotide assay and LuminexTM Multiplex Technology. RESULTS: The most common HLA-B allele was HLA-B*15:02 (41.7%) followed by HLA-B*58:01 (25%) and HLA-B*46:01 (15%). Of the 25 patients possessing HLA-B*15:02 allele, culprit medicines were carbamazepine (13 patients; 52%), traditional medicine (two patients; 8%), and unknown drugs (seven patients; 28%). Of the 15 patients carrying HLA-B*58:01 allele, there were 13 patients whose offending medicine was allopurinol. Of the eight patients whose culprit drug was traditional medicine, there were 6 patients (75%) carrying HLA-B*51:02. Patients who carry HLA-B*15:02 were found to have 4 times higher risk of developing carbamazepine-induced SJS/TEN as compared with the tolerant control group (OR=4.17; 95% CI=2.07–8.37; p < 0.001). CONCLUSION: HLA-B*15:02 was the most common HLA-B allele in Vietnamese patients with SJS/TEN. In traditional medicine-induced SJS/TEN patients, HLA-B*51:02 allele might play an important role. The link between the HLA-B genotypes and causative drugs may suggest physicians to avoid risk medications for certain patients.